The Effectiveness of Cognitive-Behavioral Therapy (CBT) on Maladaptive Early Schemas and Symptoms of Obsessive-Compulsive Disorder (OCD) in Married Women - Dinarvand, Zahra; Memari, Samira (Applied Family Therapy Journal (AFTJ), 2025)
This study aimed to evaluate the effectiveness of Cognitive-Behavioral Therapy (CBT) in reducing obsessive-compulsive symptoms and modifying early maladaptive schemas in married women aged 18 to 25 years diagnosed with obsessive-compulsive disorder (OCD).Methods: This research was conducted as a randomized controlled trial (RCT) with a pre-test, post-test, and five-month follow-up design. A total of 30 married women aged 18 to 25 years residing in Tehran were selected and randomly assigned to either the CBT intervention group (n = 15) or a waitlist control group (n = 15). The intervention group participated in 12 weekly CBT sessions (60-90 minutes each), while the control group received no intervention during the study period. Data were collected using the Young Schema Questionnaire-Short Form (YSQ-SF) to assess maladaptive schemas and the Yale-Brown Obsessive Compulsive Scale (Y-BOCS) to measure OCD symptom severity. Statistical analysis was conducted using repeated-measures ANOVA and Bonferroni post-hoc tests in SPSS-27 to evaluate changes in symptoms and cognitive patterns over time.Findings: The ANOVA results showed a significant time effect (F = 124.68, p < 0.001) on both OCD symptoms and maladaptive schemas, with participants in the CBT group demonstrating substantial reductions in both variables from pre-test to post-test and sustained improvements at follow-up. The Bonferroni post-hoc test confirmed significant differences between pre-test and post-test (p < 0.001) and pre-test and follow-up (p < 0.001) in both OCD symptoms and schemas, indicating that CBT led to both immediate and long-term benefits.Conclusion: The results suggest that CBT is an effective intervention for reducing OCD symptoms and modifying maladaptive schemas in young married women, with treatment effects persisting over time.